HYDRODYNAMIC MODEL OF SOLOTVYN ROCK SALT DEPOSIT - Шехунова, С.Б.; Негода, Ю.О.; Стадніченко, С.М.; Шестопалов, В.М.; Руденко, Ю.Ф.; Сюмар, Н.П. (Institute of Geological Sciences, NAS of Ukraine, 2023)
Rock salt development brings risks of harmful impact on water resources, in particular the Tysa River, posing a threat of cross-border spread of saline pollution on the border between Ukraine and Romania (Solotvyn rock salt deposit, Transcarpathia, western Ukraine). The impact of technogenic load (underground mining of rock salt) within the deposit led to deformation of the structure and nature of water exchange, intensification of suffusion and karst processes, ground surface deformations, catastrophic inflows of groundwater into mines, and, as a result, to the cessation of development of this deposit in 2010. However, the suspension of salt mining did not stop the development of the above-mentioned hazardous geological processes caused by both natural and man-made factors. In order to justify measures for prevention pollution of the Tysa River basin, a hydrogeological model of the Solotvyna rock salt deposit and surrounding areas was created, which allowed to predict the direction and flow rate of fresh and saline groundwater. The model was developed using new data on the geological structure and hydrogeological conditions of the study area (groundwater monitoring data). The modernised hydrodynamic model includes five layers (main aquifers and confining layers). As a result of modelling, maps of the velocity vectors and head contours for two aquifers (Quaternary and Tortonian) were obtained. Based on the results of solving a number of inverse problems, the functional correspondence of the model to natural and anthropogenic conditions was proved. According to the preliminary calculations of the actual groundwater filtration velocity and the path lines of the inert pollutant spreading, it was found that the time of its migration from the salt contour to the Tysa River is approximately 2–3 years. The developed groundwater flow model will be used to substantiate the network of hydrological and hydrogeological observation points in order to optimise the monitoring of water pollution processes.